2018
DOI: 10.1590/0004-282x20180131
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor cerebri in childhood and adolescence: data from a specialized service

Abstract: Objective: To report cases of children and adolescents diagnosed with pseudotumor cerebri associated or not with rheumatic disease. Methods: This was a retrospective study based on medical reports of 29 patients, up to 18 years of age and diagnosed with pseudotumor cerebri, followed up in the Pediatric Rheumatology and Neurology outpatient clinics of a tertiary hospital, until December 2016. Results: Among the 29 patients diagnosed with pseudotumor cerebri, 51.7% were girls and the mean age at the disease on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(27 reference statements)
4
5
0
Order By: Relevance
“…In our study, we found a higher prevalence of primary pseudotumor, that is, idiopathic intracranial hypertension in 28 patients (93.3%). There was a predominance of females in different age groups, which corroborates the literature (Balbi et al, 2018;Phillips, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, we found a higher prevalence of primary pseudotumor, that is, idiopathic intracranial hypertension in 28 patients (93.3%). There was a predominance of females in different age groups, which corroborates the literature (Balbi et al, 2018;Phillips, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The mean age for diagnosis and onset of IIH was lower than that found in other studies, IIH (n=28) was 9 years old and the youngest patient was one year old (Cleves, 2018;Balbi, 2018;Philips, 2012;Medina et al, 2014). As it is a pediatric reference center, there may have been an early referral, in addition to greater ease and agility in performing specific exams.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It is an uncommon condition affecting one in 100,000-150,000 children [ 3 ]. About 60% of children who present the syndrome are older than 10 years, and the frequency rises between the ages of 12 and 15 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%